BULLYING AND VICTIMIZATION OF CHILDREN WITH COMMUNICATION DISORDER IN PUBLIC SCHOOLS OF PORTHARCOURT LOCAL GOVERNMENT AREA RIVERS STATE - Ezevunwo, Obinachi Wori; Egbuchu, Samuel Aleruchi; Enock, Bestman (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2023)
This study investigated bullying and victimization of children with communication disorder in public primary schools in Port Harcourt Local Government Area of Rivers State. The study was guided by four objectives, four research questions and four hypotheses. A descriptive survey design was used to carry out the study. The population of this study consisted of 15,165 pupils from forty-one (41) public primary schools in the study area. The sample of the study consists of 186 pupils selected from ten (10) public primary schools, through a purposive sampling technique. A researcher designed questionnaire tagged; Communication Disorder Bullying Victims Questionnaire (CDBVQ) was used for the data collection for the study. Frequency, percentage and mean statistics were used to answer the research questions while the hypotheses were tested using chi-square at 0.05 level of significance. Findings from this study showed that the extent of the prevalence of bullying and victimization among young children with communication disorder in public primary schools is significant, the nature of bullying and victimization among young children with communication disorder in public primary schools is significant, the risk factors of bullying and victimization among young children with communication disorder in public primary schools are significant, there is significant influence of gender on the prevalence of bullying and victimization among children with communication disorder. Based on the findings of the study, it was recommended amongst others that schools administrators need to be vigilant in identifying lower levels of bullying and victimization that may still have detrimental effects on children with communication disorder.